2014
DOI: 10.1088/0952-4746/34/2/n7
|View full text |Cite
|
Sign up to set email alerts
|

A practical guideline for the release of patients treated by I-131 based on Monte Carlo dose calculations for family members

Abstract: We recently published effective doses per time-integrated activity (mSv MBq(-1) s(-1)) for paediatric and adult family members exposed to an adult patient released from hospital following I-131 therapy. In the present study, we intend to provide medical physicists with a methodology to estimate family member effective dose in daily clinical practice because the duration of post-radiation precautions for the patient-family member exposure scenario has not been explicitly delineated based on the effective dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…The gamma exposure rate constant used was 59.5 μSv/h/GBq or 2.2 R/h/mCi [2]. The ion chamber response was within 4% of the expected calculated dose rate using the point source method.…”
Section: Dose Rate Metermentioning
confidence: 88%
“…The gamma exposure rate constant used was 59.5 μSv/h/GBq or 2.2 R/h/mCi [2]. The ion chamber response was within 4% of the expected calculated dose rate using the point source method.…”
Section: Dose Rate Metermentioning
confidence: 88%
“…Some Researchers [24] suggested that a female patient treated with 5550 MBq for thyroid cancer should not hold her newborn child for at least 15 days following hospital discharge. The South African Department of Health [25] gave conditions for using radioactive nuclides.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment dosimetry prior to I-131 treatment for patients with differentiated thyroid cancer has been shown to optimize the dosing regimen in terms of the effectiveness and safety [20]. Further, patient-specific dosimetry using I-124 mIBG PET/computed tomography (CT) imaging and the Monte Carlo method has been reported for treatment planning [21], and the effective doses per time-integrated activity for pediatric and adult family members exposed to an adult patient released from hospital following I-131 therapy [22], as well as the appropriate guidelines, have also been previously reported [23]. Furthermore, radiation dosimetry and preliminary therapy results using an I-124/I-131 small molecule (MIP-1095) targeting prostatespecific membrane antigen for prostate cancer therapy have also been described [24].…”
Section: Discussionmentioning
confidence: 99%